Effects of non-genetic factors on growth traits and age at first lambing in Corriedale sheep - BABA, MOHMMAD ASHRAF; GANAI, T A S; ALAM, SAFEER; RATHER, MUBASHIR ALI; HAMADANI, AMBREEN (The Indian Journal of Animal Sciences, 2020)
Data pertaining to Corriedale sheep (4,367 birth records) spanning over a period of 25 years from 1989 to 2013 was analyzed with the Mixed Model Least Square and Maximum Likelihood algorithms to assess fixed effects of year, sex, type of birth and age of dam on various growth traits and age at first lambing. The averages were 3.69, 12.16, 17.65, 22.45, 34.59 and 893.41 for birth weight (BW), weaning weight (WW), 6 month body weight (W6), 12 month body weight (W12), 18 month body weight (W18) and age at first lambing (AFL) respectively. The overall least square means (kg) for BW, WW, W6, W12, W18 and AFL (day) were 3.20±0.091, 11.05±0.408, 16.06±0.452, 21.69±0.722, 33.425±0.776 and 882.50±11.33 respectively. Year of birth had a highly significant influence on all the studied traits. The effect of type of the birth was significant on BW, WW, W6 but non-significant on W12, W18 and AFL. Sex of the lamb had a significant effect on BW, WW, W6 and W12 and non-significant effect on W18. Dam age had a significant effect on all the body weight traits except W18. It also had a significant effect on AFL. The overview of the study reveals that the non-genetic factors affected growth traits and age at first lambing therefore should be taken into consideration while evaluating the performance of the animals. The germplasm of the Corriedale breed which is a mutton breed of sheep can be improved by selection of good animals and improving the management conditions.